Pengaruh Penerapan Metode SQ3R Terhadap Keterampilan Membaca Pemahaman Siswa Kelas V SD Negeri 1 Made Lamongan - Wulan Ayu Fitriyah; Nilamsari Damayanti Fajrin (Universitas Maritim AMNI Semarang, 2024)
This research is quantitative research. The purpose of this research is to determine the significant influence of the SQ3R method on students' Reading Comprehension Ability. The research design used in this research is Quasi Experimental Design. The sample used in this research used a non-probability sampling technique with a sample size of 40 students. This research data collection uses observation and tests. The results of this research indicate that the SQ3R method influences the reading comprehension ability of class V students at SD Negeri 1 Made Lamongan. Based on the calculation of the hypothesis test with the results of the t-test of 2 paired samples (Paired Samples), a significance value of 0.046 was obtained. Based on the test criteria if the Sig. (2-tailed) <0.05, the significance value is 0.046 <0.05, then H0 is rejected and Ha is accepted, which means that there is an influence of the SQ3R method on students' reading comprehension skills. The implementation of learning using the SQ3R method is carried out with very good criteria. an average of 95%.